Factors Affecting Performance in Companies with High Agency Costs - Linda Linda; Cut Afrianandra; Ana Fitria; Aida Yulia (Journal of Accounting Research, Organization and Economics, 2020)
Objective – This research focuses on manufacturing companies with high growth rates, as measured by the Tobins'Q proxy. The high growth of a company is closely related to higher agency costs, compared to companies with low growth rates. We investigate the influence of the board of commissioners, directors, audit committees, bid-ask spreads on the high agency costs of manufacturing companies listed on the Indonesia Stock Exchange. The indicator of agency costs in this study are the EXPR and AUR ratios.  Design/methodology – The population of this study are manufacturing companies listed on the Indonesia Stock Exchange. Purposive random sampling resulted 111 samples of companies with high growth rates. This study uses multiple linear regression analysis. The first analysis with EXPR independent variable and the second analysis with AUR independent variable, both variables could be used as agency cost indicators.  Results – The result reveals that the board of commissioners and directors have a positive effect on the agency costs, which are measured by the EXPR and AUR ratios while the audit committee has a negative significant effect on the high agency costs as measured by the EXPR ratio. Moreover, bid-ask spread as a control variable has a significant positive effect on AUR. The presence of monitoring quality, pressure, reputation of the board of commissioners and audit committee will reduce the types of management policy which may increase agency conflict.